Implementasi Kursus Pra Nikah dalam Mengurangi Angka Perceraian di Kua Pringsewu - Afrizal, Afrizal (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2017)
In Pringsewu district, divorce rates are still high. Since 2013, there were 80 divorce cases, in 2014, 89 and in 2015, 6380 divorce cases. Preservation of a marriage is not only sought after the occurrence of problems in the household, but it need before the wedding. Based on the Decree of the Director General of Islamic Guidance No. DJ.II / 542 of 2013, the Pre-Marriage Course conducted by BP4 for the bride and groom. This article describe the implementation of Pre-Marriage Courses in Pringsewu District KUA and its impact in reducing divorce rates. The conduct of Pre-Marriage Courses is still lacking or not optimal; either in terms of institutions, executors or resource persons, pre-facilities, financing, participants, and course materials. Pre-Marriage Course Policy has a stake in reducing the divorce rate, and encouraging the establishment of a sakinah family in the area